IMPLEMENTASI KEBIJAKAN PENCEGAHAN JUDI ONLINE APARATUR SIPIL NEGARA DI KANTOR OTORITAS BANDAR UDARA WILAYAH V MAKASSAR - Arfah, Arfah; Hamid, Muliyadi; Insan, Andi Nur (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The purpose of this study is to analyze the implementation of online gambling prevention policies among civil servants at the Airport Authority Office Region V Makassar, and to examine the organizational and individual responses of civil servants at the Airport Authority Office Region V Makassar. This research employs a qualitative method, which focuses on gaining an in-depth understanding of social phenomena, experiences, behaviors, or perceptions of individuals or groups within the Airport Authority Office Region V Makassar. The research sample was determined using purposive sampling, resulting in seven informants who were interviewed, with the validity and reliability of the data having been tested. The findings of this study indicate that: (1) transformational leadership style has a positive and significant effect on employee performance at the Airport Authority Office Region V Makassar; (2) organizational culture does not have a positive effect on employee performance when examined partially at the Airport Authority Office Region V Makassar; and (3) simultaneously, transformational leadership style and organizational culture have a significant effect on employee performance at the Airport Authority Office Region V Makassar.